1997
DOI: 10.1046/j.1365-2141.1997.3213138.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis fungoides and Sezary syndrome are not associated with HTLV‐I infection: an international study

Abstract: Summary. Association between mycosis fungoides (MF), its leukaemic variant Sezary syndrome (SS) and the human Tcell lymphotropic virus type-I (HTLV-I) has been controversial, with the reported incidence of infection varying between 0% and nearly 100%. We studied 127 patients (85 MF, 28 SS, five Sezary cell leukaemia, four lymphomatoid papulosis, and five unspecified cutaneous T-cell lymphomas (CTCL)) originating from Europe (France, Spain, U.K., Portugal) or from U.S.A. (California) for the presence of HTLV-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 21 publications
1
35
1
Order By: Relevance
“…Increased levels of wild-type p53 with a longer half-life have been demonstrated by immunoprecipitation in IL-2-independent cell lines with no evidence for gene mutation (Reid et al, 1993;Gartenhaus & Wang, 1995). However, in our experience, T-PLL and Sezary syndrome are not associated with HTLV-1 infections (Bazarbachi et al, 1997;Pawson et al, 1997). In some cases of non-Hodgkin lymphoma, p53 overexpression has been observed without detectable p53 gene mutation, and the transactivating function of the protein is retained, resulting in increased p21 expression (Mansukhani et al, 1997).…”
Section: Discussionmentioning
confidence: 87%
“…Increased levels of wild-type p53 with a longer half-life have been demonstrated by immunoprecipitation in IL-2-independent cell lines with no evidence for gene mutation (Reid et al, 1993;Gartenhaus & Wang, 1995). However, in our experience, T-PLL and Sezary syndrome are not associated with HTLV-1 infections (Bazarbachi et al, 1997;Pawson et al, 1997). In some cases of non-Hodgkin lymphoma, p53 overexpression has been observed without detectable p53 gene mutation, and the transactivating function of the protein is retained, resulting in increased p21 expression (Mansukhani et al, 1997).…”
Section: Discussionmentioning
confidence: 87%
“…Because of the striking similarities of CTCL spectratypes and HIV-1 spectratypes, we favor the first possibility. Previous reports implicating the lymphotropic retrovirus HTLV-1 (human T-cell lymphotrophic virus type 1) in CTCL have so far remained conflicting, 41,42 but involvement of a virus related to HTLV-1 remains a possibility. The precise nature of such a putative agent is the subject of intensive study.…”
Section: Discussionmentioning
confidence: 99%
“…Zucker-Franklin et al (31) reported the release of retroviral particles from cultured lymphocytes of 18 MF patients. However, to date, there is no convincing evidence for an involvement of either human T-cell Lymphotropic Virus Type-I nor human Herpesvirus 8 in the pathogenesis of MF (32,33). Patients with HL show defects in cellmediated immunity that can precede the development of the disease (34).…”
Section: Discussionmentioning
confidence: 99%